Pembuatan Bibliografi Beranotasi Skripsi Akuntansi Tahun 2015-2018 di Perpustakaan AKBP-STIE â€œKBPâ€ Padang - Pratama, Edo; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractThis paper discusses the 2015-2018 Accounting Thesis Annotation of Accounting Thesis at the STIE-AKBP Library in Padang. This paper aims to help users and librarians to retrieve information using a means in the form of bibliography. The purpose of writing describes the creation of an annotated bibliography of accounting theses at the STIE-AKBP Padang library. The writing of this paper uses descriptive method. Data obtained from direct collection, which is looking for physical forms of collections in the library. Based on data analysis, the following points are concluded. (1) determination of bibliographic titles; (2) collection of library materials or information tracking, which is carried out by direct search; (3) the selection of library materials, aims to determine the theme of the book to be bibliographically made; (4) grouping or classification, which the bibliography aims to describe the main problems in the book; (5) the making of keywords, aims to describe the issues in the book; (6) index preparation, in which the index taken is the author index, title index, and keyword index; (7) the creation or typing of a bibliographic script, must be in accordance with the rules that have been determined; (8) final bibliographic manuscript examination, in the form of written examination of spelling and punctuation errors, and abbreviations and reversals of the author's adjusted name.Keywords: annotated bibliography, index.